Uporabniška perspektiva v praktičnem usposabljanju na Fakulteti za socialno delo - Videmšek, Petra (Socialno delo, 2019)
In the last decade, the Faculty for Social Work, University of Ljubljana, reformed students' placement in order to ensure that they are better equipped with practical knowledge needed for becoming competent social workers. Basic changes that were made in practical placement are outlined as well as the role that experts-by-experience have played in this process. How experts-by-experience experienced their bigger role in the evaluation of students' competency in placement is shown. The authors claim that experts-by-experience are the best teachers and that their perspective can support students to become more competent social workers. They also consider the meaning of users' perspective and address why it is central to social work. Based on the theoretical belief that emphasises the importance of involving experts-by-experience in all aspects of social work education, they highlight why it is important for the perspective of experts-by-experience to be represented in practice placement and how it can contribute to the personal and professional development of students at the Faculty of Social Work.
Keywords: Fakulteta za socialno delo; izkustveno učenje; mentorji; praktično usposabljanje; socialna vključenost; socialno delo; učni načrti